Deammonification process in municipal wastewater treatment: Challenges and perspectives. (January 2021) - Gao, Dawen; Xiang, Tao
Highlights: Low concentration fluctuation is crucial for mianstream deammonification stability. Combination of autotrophy and organotrophy groups are favorable for deammonification. Deammonification can be used as an auxiliary means of multi-path nitrogen removal. Abstract: The deammonification process has been proved to be an efficient nitrogen removal process in treating high NH4 + -N concentration wastewater (sidestream deammonification). It is very hopeful to bring WWTP close to energy autarky. However, the feasibility of applying mainstream deammonification to sewage treatment need to be further explored. Therefore, this review attempts to give an overview of challenges in applying mainstream deammonification and to discuss the impacts of unfavorable conditions on main functional species. In addition, some novel control strategies to maintain the dominant position of desired species were summarized. Efficient solution to the conflict between AnAOB (Anaerobic ammonium-oxidizing bacteria) biomass retention and NOB (Nitrite oxidizing bacteria) wash out was also reviewed. Ultimately, we suggested further studies including effective improved process that achieve combination of autotrophy and organotrophy species based on the metabolic diversity of AnAOB.